Screening of carpobrotus edulis extracts for anticancer activity against cervical cancer cells - Phoogole, Walter (My University, 2024)
Introduction: Cancer is a primary cause of death and a significant impediment towards extending the life expectancy of human-kind. In terms of both incidence and fatality rates, cervical cancer is the fourth most common malignancy after lung cancer, breast cancer and colorectal cancer, worldwide. It is the second most common cancer and the primary cause of cancer fatalities in South African women. This cancer is primarily attributed to the cancer-causing Human papilloma virus (HPV). However, not all cases of cervical cancer are credited to this oncovirus. The soaring numbers can be ascribed to both inefficiencies associated with the current therapeutic strategies that are also related with adverse effects, and inadequacies linked to cancer diagnostic tools. Therefore, the development of novel anticancer medicines with improved efficacy and fewer side effects is critical. Thus, this study was aimed at evaluating the potential anticancer activity of Carpobrotus edulis extracts (C. edulis) against different cervical cancer cell lines. Methodology: C. edulis extracts were screened for the presence of various phytochemicals using the standard conventional phytochemical tests. The potential antioxidant activities of the plant extracts were quantified using both the 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) and ferric reducing antioxidant power (FRAP) assays. The probable identities of the compounds found in C. edulis extracts was determined utilizing the Liquid Chromatography-Mass Spectrophotometry (LC-MS) for identification of compounds in C. edulis. The 3-(4,5-dimethyl-thiozol-2yl)-2,5-diphenyltetrazolim bromide (MTT) assay was utilized to assess the effects of the C. edulis extracts on HeLa, CaSki and non-cancerous (Hek-293) cell lines. To further validate the cytotoxic effects of the extracts (IC50s) against the mentioned cells, the Muse™ Count & Viability assay was utilized. The Annexin V Apoptosis analysis was employed to investigate the potential cell death-inducing capacity of the C. edulis water extract against the cervical cancer cells. Furthermore, the proteome profiler human angiogenesis array was used to examine the potential effect of the water extract of C. edulis on angiogenesis in cervical cancer cell lines. xviii Results and Discussion: All the extracts were proven to possess various phytochemicals. C. edulis root extracts (acetone and ethanol) promoted the viability of cervical cancer cells while the aqueous extract had reduced the viability of both HeLa (IC50 = 1000μg/mL) and CaSki (IC50 = 1000μg/mL) cells but showed no effect against the non-cancer cells (Hek293).. The C. edulis aqueous extract induced minimal apoptosis in both CaSki (7.950 ± 1.422) and HeLa (8.933 ± 0.361) cells studied. C. edulis root water extract (1000 μg/ml) treated cells had higher levels of urokinase type-plasminogen activator (uPA), and vascular endothelial growth factor (VEGF) was somewhat higher in C. edulis root water extract treated cells than in curcumin-treated and untreated cells. Conclusion: The C. edulis root water extract was found to have potential anticancer effects on HeLa and CaSki cells, but safe against non-cancerous Hek-293 cells. Extracts from the roots of C. edulis in acetone or ethanol did not have any cytotoxic effects on HeLa or CaSki cells. HeLa or CaSki cell death were unaffected by the C. edulis root water extract, while VEGF and uPA protein levels, which promote angiogenesis, were modestly elevated.
Thesis (M. Sc. (Biochemistry)) -- University of Limpopo, 2024
Keywords: Carpobrotus edulis; Phytochemicals; Cervical cancer; Apoptosis; Angiogenesis; Proteins; Carpobrotus; Botanical chemistry; Antineoplastic agents; Cervix uteri -- Cancer